Analisis Gerak Shooting Three Point Basket Pada Pemain Klub Dubas Di Kabupaten Magelang - Tania Arlita Safitri Prastiwi; Fajar Awang Irawan (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
Basketball is a sport game that is played in groups where each group consists of 5 players. This sport is played by getting the ball into the ring as much as possible. One technique to score points is shooting. The shooting that scores the most points is the three-point shooting. The purpose of this research is to analyze the motion of three-point shooting to achieve an effective and efficient movement. The type of research used is descriptive quantitative by analyzing the principles of kinematics in biomechanics. To perform an analysis of the kinematics principle using the kinovea software version 0.9.4. The research sample was the male U-21 athletes of the Dubas club in Magelang Regency, totaling 10 people. The results obtained in this study were the average elbow angle of the preparation phase was 69.30o with an average leg angle of 103.04o. In the release phase, the average shoulder angle produced is 113.52o with an average leg angle of 166.68o. In the follow-through phase, the average elbow angle produced was 170.52o with an average shoulder angle of 134.83o and an average leg angle of 164.27o. The average jump height is 0.54m with an average maximum ball height of 6.05m. The most effective preparatory phase angle is at or close to 90o. The most effective shoulder angle in the release phase is 108o-111o. Jump height affects the effectiveness of three-point shooting.